2007
DOI: 10.1037/0893-3200.21.4.714
|View full text |Cite
|
Sign up to set email alerts
|

Emotional exchange in mother-child dyads: Stability, mutual influence, and associations with maternal depression and child problem behavior.

Abstract: This study examined the stability of the child and maternal affective expression and maternal responsiveness and the mutual influence of child and maternal expression of emotion. The authors tested whether maternal depression and child problem behavior were associated with the pattern of emotional exchange within the mother-child dyads. The sample consisted of 69 mother-child dyads (children aged 2-5 years), with 32 of the mothers having childhood-onset depression. Mothers were mostly stable in their affective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
64
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 73 publications
4
64
1
2
Order By: Relevance
“…These findings are consistent with recent theoretical work suggesting that more similar neural states allow individuals to connect and be attuned to their environment in a more harmonious way (Wheatley et al, 2012). Importantly, we also found that the degree of neural similarity in parent-child dyads promotes youths’ psychological adjustment, consistent with previous evidence showing that dyadic similarity and synchrony is a key factor in promoting youths’ positive adjustment throughout development (Barber et al, 2001; Boyum and Parke, 1995; Carson and Parke, 1996; Feldman, 2007b; Feng et al, 2007; Harrist and Waugh, 2002; Lindsey et al, 2008). Our findings indicate that children and parents’ emotional connection occurs at the neural systems level, and highlights the brain’s functional plasticity (i.e., tuned functional architecture of brain) derived from interpersonal experiences in supporting youths’ positive adjustment.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with recent theoretical work suggesting that more similar neural states allow individuals to connect and be attuned to their environment in a more harmonious way (Wheatley et al, 2012). Importantly, we also found that the degree of neural similarity in parent-child dyads promotes youths’ psychological adjustment, consistent with previous evidence showing that dyadic similarity and synchrony is a key factor in promoting youths’ positive adjustment throughout development (Barber et al, 2001; Boyum and Parke, 1995; Carson and Parke, 1996; Feldman, 2007b; Feng et al, 2007; Harrist and Waugh, 2002; Lindsey et al, 2008). Our findings indicate that children and parents’ emotional connection occurs at the neural systems level, and highlights the brain’s functional plasticity (i.e., tuned functional architecture of brain) derived from interpersonal experiences in supporting youths’ positive adjustment.…”
Section: Discussionsupporting
confidence: 90%
“…Depressed adults exhibit heightened negative and low positive emotionality (Clark & Watson, 1991; Perils et al, 2005). Prior studies have indicated that negative emotional expressiveness in depressed adults is linked with children's dysregulation and maladjustment (Feng, Shaw, Skuban, & Lane, 2007; Goodman, Adamson, Riniti, & Cole, 1994). Parental negative emotionality is also related to negative child and family functioning (e.g., Fosco & Grych, 2007; Halberstadt, 1983; Laible, 2006; Wong, McElwain, & Halberstadt, 2009).…”
Section: Parental Emotional Expressivenessmentioning
confidence: 99%
“…Parents are also supported in taking delight in their children, or responding to their children with genuine positive affect and enjoyment, for example, smiling and laughing in response to children's behavior. Although data are more limited in linking delight to child outcomes, research on similar constructs, such as shared positive affect (e.g., Kochanska & Afkan, 1995) and maternal responsiveness to child positive affect (e.g., Feng, Shaw, Skuban & Lane, 2007), suggest that delight may also play a role in children's development of behavioral and emotional regulation. Finally, parents are helped to recognize and inhibit intrusive or threatening behaviors that could be frightening to their children.…”
mentioning
confidence: 99%